Small worlds : exploring the 60 moons of our solar system - Kelch, Joseph W., 1958- (Englewood Cliffs, NJ : J. Messner, 1990)
Discusses the origin and characteristics of each of the moons circling the planets of the solar system and presents information on both manned and unmanned space exploration.
Includes index.
Keywords: Satellites -- Juvenile literature; Satellites; Outer space -- Juvenile literature. -- Juvenile literature; Outer space -- Exploration